2022
DOI: 10.3390/ijerph19148377
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Chinese Public’s Perception of Omicron Variants on Social Media: LDA-Based Topic Modeling and Sentiment Analysis

Abstract: The COVID-19 pandemic caused by SARS-CoV-2 is still raging. Similar to other RNA viruses, SARS-COV-2 is constantly mutating, which leads to the production of many infectious and lethal strains. For instance, the omicron variant detected in November 2021 became the leading strain of infection in many countries around the world and sparked an intense public debate on social media. The aim of this study is to explore the Chinese public’s perception of the omicron variants on social media. A total of 121,632 point… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…Use this research method to study academic papers in the eld of health, focusing primarily on COVID-19 [ 24][25][26] [27] , attitudes toward lesbians and gay men [ 28] , psychology, such as depression[ 29] [30] , personality traits [ 31] , group cohesion [ 32] etc. So there is originality in using this research method to study the topic of "Industrial Workers' Health".…”
Section: Discussionmentioning
confidence: 99%
“…Use this research method to study academic papers in the eld of health, focusing primarily on COVID-19 [ 24][25][26] [27] , attitudes toward lesbians and gay men [ 28] , psychology, such as depression[ 29] [30] , personality traits [ 31] , group cohesion [ 32] etc. So there is originality in using this research method to study the topic of "Industrial Workers' Health".…”
Section: Discussionmentioning
confidence: 99%
“…The present study used the LDA for topic analysis of negative sentiment posts. The LDA is a popular topic-mining method (Xie et al, 2021 ; Ogbuokiri et al, 2022 ; Oliveira et al, 2022 ; Wang H. et al, 2022 ). However, it was difficult to determine the optimal number of topics.…”
Section: Discussionmentioning
confidence: 99%
“…Oliveira et al ( 2022 ) analyzed English Twitter feeds from 12 countries from January 2020 to April 2021, and found that the main negative emotions were fear and sadness. Wang H. et al ( 2022 ) studied public sentiment related to the Omicron variant on Sina Weibo and found that fear accounted for the largest proportion of negative emotions. These studies suggest that fear may be one of the more important negative emotions during an epidemic.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Their study performed data gathering from platform of Twitter for the time-frame from 3rd Dec. 2021 to 26th Dec. 2021. A research paper introduced by Wang et al ( 2022 ) aimed at exploring the public’s perception of Chines people against Omicron variant. They used data collected from Weibo for the time frame from 27 November 2021 to 30 March 2022, using LDA-based topic modeling and ontology of DLUT emotion.…”
Section: Related Workmentioning
confidence: 99%